PATTERNS USED IN EMBROIDERY AND PATTERN ELEMENTS - Artikova Ozoda Sharofovna (The Conference Hub, 2025)
This article provides extensive information about the artistic decoration of a wide range of clothing and sewing items, that is, sewing embroidery elements. At the same time, important ideas about the importance of artistic decoration of dresses were noted.
Keywords: embroidery, decoration, fabric, knitting, leather, felt, cardboard, brick, sozana, jewelry, flower quilt, sheet.